2000
DOI: 10.1007/s007800050002
|View full text |Cite
|
Sign up to set email alerts
|

Arbitrage-free discretization of lognormal forward Libor and swap rate models

Abstract: Abstract. An important recent development in the pricing of interest rate derivatives is the emergence of models that incorporate lognormal volatilities for forward Libor or forward swap rates while keeping interest rates stable. These market models have three attractive features: they preclude arbitrage among bonds, they keep rates positive, and, most distinctively, they price caps or swaptions according to Black's formula, thus allowing automatic calibration to market data. But these features of continuous-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(49 citation statements)
references
References 24 publications
1
48
0
Order By: Relevance
“…The question of discretization of (9) is investigated by Glasserman and Zhao (1999), where it is shown that there are advantages to discretizing SDEs for de¯ated bond prices (or their increments) rather than the forward LIBOR rates themselves. Dierentiating these SDEs leads to a set of derivative SDEs analogous to (10) and it is possible to simulate a discrete-time approximation to those.…”
Section: Exact Pathwise Methodsmentioning
confidence: 99%
“…The question of discretization of (9) is investigated by Glasserman and Zhao (1999), where it is shown that there are advantages to discretizing SDEs for de¯ated bond prices (or their increments) rather than the forward LIBOR rates themselves. Dierentiating these SDEs leads to a set of derivative SDEs analogous to (10) and it is possible to simulate a discrete-time approximation to those.…”
Section: Exact Pathwise Methodsmentioning
confidence: 99%
“…The question of calibration is addressed by Rebonato (1998;1999a;1999b), advanced techniques for Monte-Carlo simulation can be found e.g. in Glasserman and Zhao (2000) and the survey article by Broadie and Glasserman (1998). On the background of this large literature we restrict ourselves to the details of the implementation that are specific to the case of credit risk modelling.…”
Section: Numerical Implementationmentioning
confidence: 99%
“…Brace, Gatarek and Musiela [1] introduced the Frozen drift approximation. Glasserman and Zhao [3] studied the arbitrage-free discretizational approximations of the LMM. Hull and White [4] , Jackel and Rebonato [5] developed the methods of approximation for the LMM by high dimensional lognormal processes.…”
Section: Introductionmentioning
confidence: 99%